The effect of director-auditor link on non-audit services fee - Malik @ Malek, Mazrah; Che Ahmad, Ayoib (Universiti Putra Malaysia Press, 2013)
Despite concerns on joint-provision of audit and non-audit services, not many studies have been conducted on examining the factors influencing companies to purchase non-audit services from their auditor. The attachment theory postulates that non-audit services purchasing decisions are influenced by the director-auditor link. Using 759 sample companies listed on Bursa Malaysia in 2007, the OLS regression results show a significant positive relationship between director-auditor link and non-audit services fee. The finding adds to the limited literature on the factors influencing companies to purchase non-audit services from their auditor and suggests the need for active involvement of shareholders in the auditor selection process.